EFFECT OF LIQUIDITY AND LEVERAGE ON PROFITABILITY IN KUD. HAPPY TANI KULIM JAYA VILLAGE, INDRAGIRI HULU REGENCY 2014-2020 PERIOD - Irawati Irawati (LPPM Press STIE Indragiri Rengat, 2021)
The purpose of this study was to determine liquidity, leverage and profitability, as well as the effect of liquidity and leverage on profitability at KUD Tani Bahagia in Kulim Jaya Village, Indragiri Hulu Regency, both simultaneously and partially. The research method used is the classical assumption test, multiple linear regression analysis. The correlation coefficient and determination as well as hypothesis testing are f-test and t-test. Where the test is carried out using spss 21. The results of the correlation test show a very strong relationship. The f test shows that liquidity and leverage have an effect on profitability. While the partial test of liquidity has an effect on profitability, while leverage has an effect but is not significant on profitability.